Biomarkers in Lake Van sediments reveal dry conditions in eastern Anatolia during 110.000–10.000 years B.P. (15th February 2017) - Randlett, Marie‐Eve; Bechtel, Achim; van der Meer, Marcel T. J.; Peterse, Francien; Litt, Thomas; Pickarski, Nadine; Kwiecien, Ola; Stockhecke, Mona; Wehrli, Bernhard; Schubert, Carsten J.
Abstract: Lipid biomarkers were analyzed in Lake Van sediments covering the last 600 ka, with a focus on the period between 110 and 10 ka, when a broad maximum in pore water salinity as a relict from the past suggests dry conditions. The occurrence and distribution of biomarkers indicative for terrestrial plants (long‐chain n‐ alkane C29 ), haptophyte algae (methyl alkenones C37 ) and halophilic archaea (archaeol) all point toward a dry climate in Lake Van region during this time interval. The hydrogen isotopic composition of C29 n‐ alkanes (δDC29 ) and C37 alkenones (δDC37 ) is enriched between MIS 4 and MIS 2, which is interpreted as a decrease in the regional ratio of precipitation to evaporation. Similarly, the low abundance of the acyclic glycerol dialkyl glycerol tetraether GDGT‐0 relative to archaeol, quantified by the Archaeol and Caldarchaeol Ecometric (ACE) is assumed to reflect the presence of halophilic euryarchaeota adapted to high salinity water. The climate around Lake Van appears in phase with the Yammouneh basin 800 km southwest and Lake Urmia 250 km southeast of Lake Van over the last two glacial periods. The results highlight the potential of combining ACE, δDC29, and δDC37 for reconstructing salinity changes and regional precipitation to evaporation ratio from lake sediments. Key Points: Low precipitation/evaporation ratio in Lake Van region during MIS 4‐2 deduced from algal and terrestrial plant biomarkers Coinciding increase of lipid hydrogen isotopic composition (δD) indicates changes in moisture availability and source High ACE index values due to low GDGT‐0 concentrations reveal the presence of halophilic euryarchaeota